2007
DOI: 10.1111/j.1462-2920.2007.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct communities of ammonia‐oxidizing bacteria along an estuarine salinity gradient

Abstract: The relationship between ammonia-oxidizing bacteria (AOB) and potential nitrification rates was examined along a salinity gradient in a New England estuary in spring and late summer over 3 years. Ammonia-oxidizing bacteria abundance was estimated by measuring gene copies of the ammonia monooxygenase catalytic subunit (amoA) using real-time polymerase chain reaction. Ammonia-oxidizing bacteria abundance ranged from below detection to 6.0 x 10(7)amoA copies (gdw sediment)(-1). Mean potential nitrification rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
105
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 57 publications
22
105
1
3
Order By: Relevance
“…Composition was highly variable over seasons and years, and compositional changes in response to the nutrient treatments were minor in comparison. High temporal variability in AOB communities (both abundance and composition) has been observed in both soils and the water column (Gray et al, 2003;O'Mullan and Ward, 2005) and in estuarine sediments (Bernhard et al, 2007;Ando et al, 2009;Fortunato et al, 2009). Given the importance of temperature on the spatial variability of AOB in soils (Fierer et al, 2009), we speculate that temperature could be one important factor contributing to this temporal variability.…”
Section: Temporal Variability and Nutrient Responsesmentioning
confidence: 88%
See 2 more Smart Citations
“…Composition was highly variable over seasons and years, and compositional changes in response to the nutrient treatments were minor in comparison. High temporal variability in AOB communities (both abundance and composition) has been observed in both soils and the water column (Gray et al, 2003;O'Mullan and Ward, 2005) and in estuarine sediments (Bernhard et al, 2007;Ando et al, 2009;Fortunato et al, 2009). Given the importance of temperature on the spatial variability of AOB in soils (Fierer et al, 2009), we speculate that temperature could be one important factor contributing to this temporal variability.…”
Section: Temporal Variability and Nutrient Responsesmentioning
confidence: 88%
“…In general, microbial community-process relationships likely depend on environmental conditions. For instance, in estuarine sediments, Bernhard et al (2007) found that the strength of the correlation between AOB abundance and potential nitrification rates varies along a salinity gradient. Finally, AOB composition was highly variable within and across years, even in untreated plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These counter results indicate that although the surrounding waters had permeated through the cages, sediment processes internal to the cages directly influenced ammonium concentrations. Microorganisms drive most processes in the nitrogen cycle, and previous studies provide evidence that their particular composition influences these processes rates (Cavigelli andRobertson, 2000, Avrahami et al, 2002;Balser and Firestone, 2005;Bernhard et al, 2007a). A related result is that sediment origin (either directly or interactively with environment) affected nitrification and methane flux, but not CO 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Most of what is known about how biodiversity varies along environmental gradients stems from research on plants and animals, although recent studies suggest that microorganisms may exhibit similar gradient patterns. Within the bacteria, for instance, diversity and composition appear to vary along gradients of primary productivity (Horner-Devine et al, 2003), latitude (Blum et al, 2004;Yergeau et al, 2007), disturbance (Johnsen et al, 2001;Muller et al, 2001), climate (Yergeau et al, 2007) and salinity (Blum et al, 2004;Crump et al, 2004;Bernhard et al, 2005Bernhard et al, , 2007. However, even less is known about the variation of fungal diversity and composition along similar gradients.…”
Section: Introductionmentioning
confidence: 99%